2017
DOI: 10.1007/s00262-017-1967-1
|View full text |Cite
|
Sign up to set email alerts
|

Combining talimogene laherparepvec with immunotherapies in melanoma and other solid tumors

Abstract: Talimogene laherparepvec is a first-in-class intralesional oncolytic immunotherapy. In a recent Phase III trial (OPTiM), talimogene laherparepvec significantly improved durable response rate compared with subcutaneous granulocyte–macrophage colony-stimulating factor (GM-CSF). Overall response rate was also higher in the talimogene laherparepvec arm, and the greatest efficacy was demonstrated in patients with earlier-stage (IIIB, IIIC, or IVM1a) melanoma. Talimogene laherparepvec was well tolerated, with the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 53 publications
0
41
0
Order By: Relevance
“…Several mouse experiments, with different types of cancer cells, reported that both CTLA-4 and PD-L1 checkpoints blockade enhanced the OV therapy [ 29 33 ]. There are also several clinical trials with OV and checkpoint inhibitors [ 34 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several mouse experiments, with different types of cancer cells, reported that both CTLA-4 and PD-L1 checkpoints blockade enhanced the OV therapy [ 29 33 ]. There are also several clinical trials with OV and checkpoint inhibitors [ 34 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the understanding of irAEs related to T‐VEC treatment is of growing importance. T‐VEC may be expanded to new indications, and investigation into combined therapy with ICIs is underway . The potential to encounter histopathologic panniculitis in either T‐VEC or ICI monotherapy means that combined therapies could produce a new spectrum of irAEs and/or unusual histopathologic findings that could occur with combined therapy.…”
Section: Discussionmentioning
confidence: 99%
“…T-VEC may be expanded to new indications, and investigation into combined therapy with ICIs is underway. 36 The potential to encounter histopathologic panniculitis in either T-VEC or ICI monotherapy means that combined therapies could produce a new spectrum of irAEs and/or unusual histopathologic findings that could occur with combined therapy. Thus, increased awareness of the various presentations of panniculitis in immunomodulatory cancer treatments such as T-VEC is essential to providing a diagnosis that is as accurate and etiologically specific as possible.…”
Section: Granulomatous Dermatitis Has Been Reported In Association Withmentioning
confidence: 99%
“…The combination of pembrolizumab and T‐VEC was postulated to enhance the systemic antitumor response by enhancing the recognition and killing of tumor cells by T cells that have been primed as a result of T‐VEC injection . This combination was first evaluated in the phase 1b portion of the Phase 1b/III clinical trial (MASTERKEY‐265) launched in 2014 .…”
Section: Systemic Therapiesmentioning
confidence: 99%